2023
DOI: 10.1002/ijgo.14909
|View full text |Cite
|
Sign up to set email alerts
|

Timing of intra‐abdominal aortic balloon occlusion for prevention of hemorrhage in patients with placenta previa and placenta accreta spectrum

Abstract: ObjectivePlacenta accreta spectrum (PAS) has been linked to severe negative maternal–fetal pregnancy outcomes, including a high risk of maternal death. The goal of this study was to determine whether an abdominal aortic balloon block performed before fetal birth lowered intraoperative bleeding and the risk of severe bleeding, as opposed to a block performed after fetal birth.MethodsIn this retrospective cohort study, patients who underwent pre‐delivery or post‐delivery inflation were compared for intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Huang et al 1 showed important findings regarding the timing of aortic balloon occlusion (ABO) in placenta accreta spectrum (PAS) surgery: before versus after infant delivery. Nevertheless, I have some questions.…”
Section: Letter To the Editor: Timing Of Intra-abdominal Aortic Ballo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al 1 showed important findings regarding the timing of aortic balloon occlusion (ABO) in placenta accreta spectrum (PAS) surgery: before versus after infant delivery. Nevertheless, I have some questions.…”
Section: Letter To the Editor: Timing Of Intra-abdominal Aortic Ballo...mentioning
confidence: 99%
“…The findings fundamentally supported this. They state some merits of pre-ABO over post-ABO: (1) to reduce bleeding at uterine and placental incisions (the latter sometimes required in uterus-preserving surgeries);…”
Section: Letter To the Editor: Timing Of Intra-abdominal Aortic Ballo...mentioning
confidence: 99%
See 1 more Smart Citation